OPTIMASI PARAMETER VACUUM ASSISTED RESIN INFUSION PRODUK FRONT TOP TERHADAP KEKASARAN PERMUKAAN - Valerian, Joey; Dwilaksana, Dedi; Syuhri, Ahmad; listyadi S, Digdo; Nashrullah, M Dimyati; Noor HS, Skriptyan (STATOR: Jurnal Ilmiah Teknik Mesin, 2023)
The use of composite materials as a substitute for metal materials in the engineering field has become increasingly widespread not only in the field of transportation panels but also in other fields such as property and architecture because alternatives have the advantage of using composite materials to be lightweight, corrosion resistant and strong and can be designed as needed. One of the methods developed to manufacture composite polymers is resin infusion with vacuum assistance. This method is inversely compared to the non-vacuum method. The (VARI) process requires an airtight space in printing and can reduce the fouling effects that occur in non-vacuum processes such as causing a lack of optimal composite material properties. The Taguchi method is a methodology in the field of engineering which is very much aimed at improving a product quality in a time process while at the same time reducing costs and minimal resources. The Taguchi method is a product or process that is robust against noise, therefore this method is a robust design. In writing this research, I have experience in the process of making and researching carbon in body organization in the Mechanical Engineering University of Jember named Tawang Alun, here I will conduct research in analyzing the optimal parameters for the surface roughness characteristics of front cover products made of carbon fiber using a vacuum process. resin infusion aid. The factor that contributes the most to the surface roughness response is vacuum pressure with a contribution of 25.20%. For hardener factor contribution of 14.93% and coating factor of 23.77%. The contribution error that occurs is 36.09%. Each factor has a value contribution that is not too different. Based on the data and analysis results that have been obtained using the Taguchi method with the help of Minitab 19 and Microsoft Excel, it shows that the parameter of vacuum pressure has a significant influence on the results of surface roughness. While the hardener parameter has no significant effect on surface roughness, then the coating parameter has a significant effect on surface roughness. In the calculation of the F test, it can be concluded that the optimal factor parameters in making a front top with a small surface roughness value are 0.4 bar vacuum pressure, 60% hardener and PVAC coating. Keywords: PVAC, vacuum, carbon fiber, resin